Pengaruh Impulsive Buying Dan Online Customer Rating Terhadap Minat Pembelian Kosmetik Dalam Perspektif Bisnis Islam (Studi Pada Konsumen Topshop Bandar Lampung) - Rohimah, siti; Nurhayati, Nurhayati (Business and Enterpreneurship Journal (BEJ), 2024)
This research is motivated by impulsive buying without thinking about buying a product. They make purchases unconsciously just because they are interested in the product without thinking about the consequences that arise afterwards. Another factor that influences impulsive or unplanned purchases is the presence of online customer ratings which can convince consumers to make purchases. The formulation of the problem in this research is, do impulsive buying and online customer ratings have a partial and simultaneous effect on interest in purchasing cosmetics? What about impulsive buying, online customer ratings and interest in purchasing cosmetics from an Islamic business perspective? The aim of this research is to determine the partial and simultaneous influence of impulsive buying and online customer ratings on interest in purchasing cosmetics among Topshop consumers from an Islamic business perspective. This research is quantitative research, the population in this research is all Topshop Bandar Lampung consumers. The sample used in this research was probability sampling with a sample of 100 people and data analysis for this research used SEM model analysis using SmartPLS version 3.0. The partial results of this research are that impulsive buying (X1) has a positive and significant effect on purchase interest (Y), and online customer rating (X2) has a positive and significant effect on purchase interest (Y). Impulsive buying and online customer rating simultaneously influence the interest in purchasing cosmetics among Topshop Bandar Lampung consumers. In the Islamic view, humans are commanded to consume halal and good goods/services in a reasonable or moderate manner. Fulfillment of desires is still permitted as long as it is able to increase benefit or does not bring harm. Keywords: Impulsive Buying, Online Customer Rating and Purchase Interes